Utilization of the field experiment results of University of Debrecen in the development of maize-based bio-ethanol production - Rátonyi, Tamás; Nagy, János; Harsányi, Endre (Acta Agraria Debreceniensis, 2012)
Maize is currently the single raw material of bio-ethanol production in Hungary. The aim of our examinations is the observation of yield and nutritional characteristics of commercial maize hybrids in Hungary from the aspect of efficient bio-ethanol production. We set up a randomized block field trial. We determined the starch content and starch yield (t ha-1) of the 51 maize hybrids involved in the field trial. In laboratory conditions, we examined the amylose and amylopectin ratio and the amount of resistant starch of the selected 20 maize hybrids. According to our results, there is a significant difference between the starch yield the amylose component of the starch content and resistant starch of the examined maize hybrids. Our studies reveal that maize as a raw material must be selected based on the cultivation objectives. If the objective is bio-ethanol production, detailed knowledge of starch content is necessary. There is a significant difference among commercial maize hybrids in Hungary in terms of characteristics determining the producible amount of bio-ethanol.